2009
DOI: 10.4319/lo.2009.54.1.0368
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying phosphorus and light effects in stream algae

Abstract: Simultaneous gradients of phosphorus and light were applied in experimental streams to develop quantitative relationships between these two important abiotic variables and the growth and composition of benthic microalgae. Algal biovolume and whole-stream metabolism responded hyperbolically to phosphorus enrichment, increasing approximately two-fold over the 5-300 mg L 21 range of experimental phosphorus concentrations. The saturation threshold for phosphorus effects occurred at 25 mg L 21 of soluble reactive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(104 citation statements)
references
References 50 publications
5
98
1
Order By: Relevance
“…Besides he recognized that light levels had the strongest effect on community composition. Hill et al (2009) also observed in experiments that light affected algal community structure much more than the phosphorus enrichment utilized. In addition, although high profile taxa are able to form colonies, which give advantageous for exploiting resources (Berthon et al 2011), these colonies may be tumbled by gross amount of suspended matters in the river.…”
Section: Temporal Studiesmentioning
confidence: 61%
See 1 more Smart Citation
“…Besides he recognized that light levels had the strongest effect on community composition. Hill et al (2009) also observed in experiments that light affected algal community structure much more than the phosphorus enrichment utilized. In addition, although high profile taxa are able to form colonies, which give advantageous for exploiting resources (Berthon et al 2011), these colonies may be tumbled by gross amount of suspended matters in the river.…”
Section: Temporal Studiesmentioning
confidence: 61%
“…This allows us to assume that it is not the nutrients inevitably which had the greatest influence on guilds proportions. Some cases can occur when such factors can have importantly roles like types of substrates or light intensity (Hill et al 2009, Lange et al 2011. For instance in some samples no diatoms were detected, or only just a few valves.…”
Section: Spatial Studiesmentioning
confidence: 99%
“…However, in this study (as in a number of other studies e.g. Hill et al, 2009;Rosemond et al, 2000) a large range in P concentration was used, and it suggests that the diatom community is resistant to major changes in water phosphorus concentrations, at least over the short time scales investigated. Furthermore, it is likely that the species pool within the River Thames is dominated by taxa adapted to high nutrient concentrations.…”
Section: Effect Of Phosphorus Concentration Changes On Periphytonmentioning
confidence: 88%
“…These numbers of mesh layers were then placed over the downstream sections of the flumes, to recreate the light intensities equivalent to these different levels of tree shading. Previous studies have successfully used similar approaches to investigate light limitation of periphyton (Hill et al, 2009). Each set of three flumes contained an unshaded, intermediate shaded (equivalent to dappled tree shade) and fully shaded (equivalent to full tree canopy cover) flume.…”
Section: Effect Of Light Intensity On Periphyton (Experiments 3)mentioning
confidence: 99%
See 1 more Smart Citation